2017
DOI: 10.3233/cbm-160117
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against heat shock proteins as biomarkers for the diagnosis and prognosis of cancer

Abstract: Thanks to their specificity and stability in the sera, autoantibodies (AAbs) against tumor-associated antigens (TAAs) are very attractive biomarkers for the development of less invasive serological tests for the diagnosis and prognosis of cancer. Heat shock proteins (HSP) belong to TAAs and they are over-expressed in various human cancers. Elevated HSP can stimulate the immune system to produce anti-HSP antibodies. So far, AAbs against HSP have been identified in the circulation of various cancer patients. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Elevated HSP can stimulate the immune system to produce anti-HSP autoantibodies (AAbs). AAbs against HSPs have been identified in the circulation of various cancer patients [156]. Because of their specificity and stability in the sera, AAbs against HSPs can be also attractive biomarkers for the development of less invasive serological tests for the diagnosis and the prognosis of cancer.…”
Section: Hsps As Biomarkers Detectable By Liquid Biopsiesmentioning
confidence: 99%
“…Elevated HSP can stimulate the immune system to produce anti-HSP autoantibodies (AAbs). AAbs against HSPs have been identified in the circulation of various cancer patients [156]. Because of their specificity and stability in the sera, AAbs against HSPs can be also attractive biomarkers for the development of less invasive serological tests for the diagnosis and the prognosis of cancer.…”
Section: Hsps As Biomarkers Detectable By Liquid Biopsiesmentioning
confidence: 99%
“…HSPs have anti-apoptotic properties and can help cancer cells evade apoptosis. Accordingly, they are overexpressed in a wide range of cancers, and this overexpression is a bad prognostic marker for some cancers [ 102 , 103 ]. Moreover, these molecules are shown to be involved in ICD.…”
Section: Origins Of Autoimmune Responses In Oncologymentioning
confidence: 99%
“…These aAbs are also observed in a wide range of autoimmune diseases including SLE and RA [ 86 ]. Anti-HSP90 aAbs in breast cancer patients are associated with a bad prognosis [ 103 ]. It was shown that an aAb against a single HSP was present in between 8%–40% of cancer patients as opposed to 1.6–25% of healthy subjects [ 103 ].…”
Section: Origins Of Autoimmune Responses In Oncologymentioning
confidence: 99%
“…Antibodies against HSPs are normally present in the serum of healthy individuals (Cohen ; Shi et al . ). The increased anti‐HspBP1 IgG levels observed in the present study may be associated with B cell activation because of the increased serum level of HspBP1.…”
Section: Discussionmentioning
confidence: 97%